Supporting Asian immigrant English language learners: teachers' beliefs and practices (IR) - Mazlina Mustafa (2014)
This phenomenological study explores the beliefs and practices of New Zealand earlychildhood teachers in supporting English acquisition for Asian immigrant English languagelearners (ELLs). The focus of the study is on the analysis of early childhood teachers' beliefsabout how they can support English acquisition among Asian immigrant ELLs and how thesebeliefs influence the teachers' practices in early childhood education (EeE) settings.The theoretical framework of this research draws on a range of sociocultural perspectives,including (i) the sociocultural positions initially defined by Lev Vygostky (1978), (ii) thenotion of guided participation articulated by Barbara Rogoff (2003), (iii) theories of secondlanguage acquisition discussed by Lantolf and Thorne (2000), and by Krashen (1982, 1985),and (iv) acculturation as addressed by Berry (2001).The main participants of this study were seven early childhood teachers and six Asianimmigrant ELLs from two EeE centres. Four Asian parents participated in interviews toascertain the parents' perspectives about their children's learning of English and theirmaintenance of home language. Research methods for the teachers included observations andsemi-structured pre- and post-observation interviews. For each centre, observations werecarried out over a six week period which enabled a series of snapshots of how the teacherssupported the ELLs as they acquired English.The findings were analysed using thematic analysis, and presented three themes:English dominance, social cultural adaptation, and guided participation. These themesimpacted the learning experiences of the Asian immigrant ELLs and other children attendingthe EeE as well as the teaching approaches of the early childhood teachers. The findingsrevealed that there were dissonances between the teachers' beliefs and their practices, as wellas variation between individual teachers' beliefs and practices. Because of a significantincrease in the number of ELLs in New Zealand EeE centres, it is important for earlychildhood teachers to understand the emphasis upon sociocultural theories in the EeEcurriculum, so that they can effectively apply these theories to their practices. This study willprovide a basis from which to consider how early childhood teachers in New Zealand candraw upon sociocultural perspectives to better support ELLs as they acquire English, whilevaluing and supporting their linguistic and cultural backgrounds